2009
DOI: 10.1029/2008jc005023
|View full text |Cite
|
Sign up to set email alerts
|

Transport estimates at the western section of the Strait of Gibraltar: A combined experimental and numerical modeling study

Abstract: Three‐yearlong time series of Acoustic Doppler Current Profiler (ADCP) observations at a single station in Espartel Sill (Strait of Gibraltar) were used to compute an outflow of Q2 = −0.82 Sv through the main channel. The cross‐strait structure of the velocity field or the outflow through a secondary channel north of the submarine ridge of Majuan in Espartel section is not captured by observations so that an improved version of a numerical model (CEPOM) has been used to fill the observational gap. Previously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 29 publications
(42 reference statements)
7
56
0
Order By: Relevance
“…In previous modeling exercises covering this time period, a similar drop in the AJ velocity and a shift southward at the end of 2007 has been described (Peliz et al 2013;Boutov et al 2014). Also, in current data from an ADCP measuring the intensity of the Mediterranean outflow within the main channel of the strait, a substantial increase in water velocity was registered for winter 2007(Sánchez-Román et al 2009). Henceforth, this event of inflow reduction (and increased outflow) reproduced by our model seems to have really happened.…”
Section: Discussionsupporting
confidence: 62%
“…In previous modeling exercises covering this time period, a similar drop in the AJ velocity and a shift southward at the end of 2007 has been described (Peliz et al 2013;Boutov et al 2014). Also, in current data from an ADCP measuring the intensity of the Mediterranean outflow within the main channel of the strait, a substantial increase in water velocity was registered for winter 2007(Sánchez-Román et al 2009). Henceforth, this event of inflow reduction (and increased outflow) reproduced by our model seems to have really happened.…”
Section: Discussionsupporting
confidence: 62%
“…The relevant amount of data has been in part exploited scientifically, also linking them with repeated CTD sections (Gasparini et al, 2005;Vargas-Yáñez et al, 2005Millot et al, 2006;Millot, 2007Millot, , 2009Palanques et al, , 2009Palanques et al, , 2012García-Lafuente et al, 2007Font et al, 2007;CIESM, 2008CIESM, , 2009Puig et al, 2008Puig et al, , 2013Sánchez-Román et al, 2009;Millot and García-Lafuente, 2011;Ribó et al, 2011). There are evidences of interannual θ and S variability in different water masses, even though most of the HC time series are still too short to significantly address issues on long-term variability and trends.…”
Section: Resultsmentioning
confidence: 99%
“…Bray et al (1995) showed that the greatest AW vs. MOWs contrast is at CAS, which points at this sill as the best place for monitoring the twolayer exchange. On the other hand, experimental (Farmer and Armi, 1988;Sánchez-Román et al, 2009) and numerical (Castro et al, 2004;Sannino et al, 2004Sannino et al, , 2009Sánchez-Román et al, 2009) studies suggest that hydraulic control on MOW is a rather permanent feature at ES, which is the last topographic constriction before they sink in the ocean down to ∼ 1000 m (Baringer and Price, 1997;Ambar et al, 2002), while at CAS the hydraulic control is lost almost every tidal cycle. This hydraulic behaviour gives ES practical advantages to compute the volume transport using a single mooring line.…”
Section: The Strait Of Gibraltarmentioning
confidence: 99%
“…However, this choice cannot be applied because of the lack of salinity profiles. An alternative solution, adopted here, is to take the depth of maximum velocity shear as the interface, as in Sánchez-Román et al (2009. In order to deal with the possible spikes in the ADCP velocity record, prior to computing flows, the current profiles have been smoothed vertically with a cubic polynomial fit with 1 m resolution and temporally with a 20 min moving average.…”
Section: Outflow Per Unit Widthmentioning
confidence: 99%